XÁC ĐỊNH MỰC NƯỚC TỐT NHẤT CHO LÚA VÀ CÁ TRONG HỆ THỐNG CANH TÁC LÚA-CÁ NƯỚC NGỌT Ở ĐỒNG BẰNG SÔNG CỬU LONG - Hà, Võ Văn; Cần, Nguyễn Duy; Nhân, Đặng Kiều (Tạp chí Khoa học Đại học Cần Thơ, 2004)
Abstract A study was conducted in theMekongDelta from 2000 to 2002 in order to (1) investigate farmers? water management practices in rice-fish farming and (2) determine appropriate water levels for rice-fish farming, in terms of rice and fish yields and economic efficiency. The study consisted of an analysis of data obtained from farm surveys followed by on-station experimentation in a controlled environment. During the farm surveys data were collected from sixty four farmers practicing integrated rice-fish farming in four districts, which were considered representative for the freshwater rice-fish farming areas in theMekongDelta. Based on the analysis of data obtained during these surveys, an on-station experiment was conducted using a randomized complete block design with four treatments (four different water levels: 5, 12, 19 and 26 cm) and two replications. The experiment was conducted in both dry and wet season. Water levels strongly influenced rice and fish yields, and profitability of rice-fish farming. Data analysis showed that water levels above 15 cm significantly decreased rice yields in the wet season crop as well as total wet season/dry season rice output, compared to lower water levels. Fish yields under water levels below 10 cm were significantly lower than yields under higher water levels. A partial cost-benefit analysis showed that water levels between 10-15 cm were most appropriate. Water levels of 10-15 cm lead to higher gains (2.85 million VND/ha/year more than water levels below 10 cm and 0.78 million VND/ha/year more than water levels above 15 cm). In the experiment, increased water levels in rice fields (above 12 cm) had an influence on some water parameters, presence of weeds, rice and fish yields. Increased water levels caused some change in day ? night variation of water temperature. Increased water levels led to lower concentrations of dissolved oxygen and chlorophyll-a and these trends depended on vegetative or reproductive stages of the rice plant. Increased water levels reduced influence water pH in the field but caused a decrease of turbidity in the trench. Increased water levels reduced total weed biomass. Furthermore, increased water levels significantly increased rice plant height, panicle weight, number of filled grains per panicle and total biomass. Increased water levels however reduced the number of panicles, harvest index of rice and hence rice yields. Fish yields, on the contrary, increased under water levels above 12 cm (263 kg/ha/crop, as compared with 209 kg/ha/crop under water levels of 5 cm). Following conclusions and recommendations can be drawn from the on-farm as well as experimental findings: Water levels in rice-fish fields should be kept between 11 and 15 cm in the wet season and between 11 and 19 cm in the dry season. The surrounding dikes should be firm enough to avoid water leakages and escaping of fish to adjacent fields. Rice fields should be well leveled in order to optimize water management, which significantly reduces weed occurrence and costs for transplanting and irrigation. Title: Determine appropriate water levels for rice-fish farming, in the freshwater rice-fish farming areas in the Mekong Delta